Immune Responses to Gram-Negative Bacteria in Hemolymph of the Chinese Horseshoe Crab, Tachypleus tridentatus - Wang, Wei-Feng; Xie, Xiao-Yong; Chen, Kang; Chen, Xiu-Li; Zhu, Wei-Lin; Wang, Huan-Ling (Frontiers in Immunology, 2021)
Chinese horseshoe crab, Tachypleus tridentatus, is an ancient marine arthropod with a long evolutionary history. As a kind of living fossil species, the pathogen defenses of horseshoe crabs entirely depend on the innate immune system. Although, there are abundant immune molecules found in the horseshoe crab hemolymph, the biological mechanisms underlying their abilities of distinguishing and defending against invading microbes are still unclear. In this study, we used high-throughput sequencing at mRNA and protein levels and bioinformatics analysis methods to systematically analyze the innate immune response to Gram-negative bacteria in hemolymph of Chinese horseshoe crab. These results showed that many genes in the complement and coagulation cascades, Toll, NF-κB, C-type lectin receptor, JAK-STAT, and MAPK signaling pathways, and antimicrobial substances were activated at 12 and 24 h post-infection, suggesting that Gram-negative bacteria could activate the hemolymph coagulation cascade and antibacterial substances release via the above pathways. In addition, we conjectured that Toll and NF-κB signaling pathway were most likely to participate in the immune response to Gram-negative bacteria in hemolymph of horseshoe crab through an integral signal cascade. These findings will provide a useful reference for exploring the ancient original innate immune mechanism.